El argumento de la locura - Porchat Pereira, Oswaldo (Pontificia Universidad Católica del Perú, 2005)
The argument explores the possible consequences of a philosopher´s critical revision of his own beliefs and certainties, in which he would consider the possibility of being mad. Although the argument is developed in the first person -with a Cartesian profile alien to the argumentative pattern of ancient Pyrrhonic scepticism- it nevertheless ends with a sceptical conclusion. It radically challenges and checkmates classical reason's ideals of certainty and absolute. Knowledge.

El argumento explora las consecuencias que habría si, en el decurso de una revisión critica emprendida por un filósofo de sus creencias y certezas, este considerase la posibilidad de estar loco. Desarrollado en primera persona, el argumento -que tiene un perfil cartesiano y es extraño al patrón de argumentación del antiguo escepticismo pirrónico- culmina, sin embargo, en una postura escéptica. Él desafía y pone en jaque, de una manera radical, los ideales de certeza y conocimiento absolutos propuestos por la razón clásica.
The Argument of Madness
Keywords: Skepticism; Certainty; Madness; Cartesian.; Escepticismo; Certeza; Locura; Cartesiano.; https://purl.org/pe-repo/ocde/ford#6.03.01